TEACHING POETRY WRITING USING THE EXPERIENTIAL LEARNING APPROACH - Suryantoro; Tinggil Elangmolyna Krisnuari; Riswanda Himawan (Universitas PGRI Palembang, 2025)
This article presents a study aimed at enhancing the poetry writing skills of Grade VIII C students at SMP Negeri 12 Malang through the implementation of the experiential learning approach. Employing a Classroom Action Research (CAR) design, the study was carried out over two iterative cycles, each encompassing the stages of planning, action, observation, and reflection. Findings from the research demonstrated a 20% improvement in students' poetry writing abilities from the first to the second cycle. These results underscore the pedagogical effectiveness of the experiential learning approach in fostering students' creative expression and written literacy in poetry. The article further elaborates on the pedagogical implications of these findings, suggesting that experiential learning can serve as a transformative instructional model in language and literature education.